Autochthonous Lacticaseibacillus rhamnosus strains as probiotic candidates: comprehensive in vitro and in silico characterization - De Gregorio, Priscilla Romina; Lieske, Isadora; Nied, Cathy; Signori, Gabriela; Kuhn, Daniel; Schmitz, Caroline; Martins, Vera Lúcia Milani; Bustamante Filho, Ivan Cunha; Irazoqui, Jose Matias; Souza, Claucia Fernanda Volken de (Elsevier, 2025)
This study aimed to identify promising probiotic candidates among 25 autochthonous lactic acid bacteria (LAB) isolates from dairy products sourced from southeastern Brazil. In vitro assays were carried out to elucidate their phenotypic profiles, focusing on key probiotic attributes (antimicrobial, antioxidant and β-galactosidase activities, resistance to simulated gastrointestinal conditions, antibiotic susceptibility, and adhesion capacity). Principal Component Analysis was subsequently employed to rank the most promising strains. Among the isolates, four Lacticaseibacillus rhamnosus strains (6QLR5, GTM7, CLM11, and JLR3) demonstrated promising antimicrobial activity, adhesion capacity, tolerance to gastrointestinal conditions, antioxidant capacity, and β-galactosidase activity. Of these, strains 6QLR5 and GTM7 displayed the most robust phenotypic probiotic profiles and were selected for in silico genomic analysis. Functional annotation revealed genes associated with key probiotic traits, including redox systems related to antioxidant activity, adhesion-associated proteins, and mechanisms of resistance and adaptation to the harsh conditions of the intestinal tract. Genomic safety assessment, encompassing antimicrobial resistance genes, mobile genetic elements, virulence factors, and genome-stability features, indicated that strains 6QLR5 and GTM7 are safe probiotic candidates, as they harbored no genes linked to antibiotic resistance, pathogenicity, or virulence, and lacked hazardous plasmids or prophages. Overall, the characterization of autochthonous LAB strains based on integrative in vitro and in silico approaches proved effective for selecting probiotic candidates.